Experimental and theoretical investigations on high power vacuum-ultraviolet laser at 165 nm by eighth-harmonic generation in KBBF. (December 2019) - Li, Yu-Jiao; Zong, Nan; Dai, Shi-Bo; Wang, Zhi-Min; Zhang, Shen-Jin; Yang, Feng; Zhang, Feng-Feng; Xu, Feng-Liang; Kou, Yang; Peng, Qin-Jun; Liu, Li-Juan; Wang, Xiao-Yang; et al.
Highlights: VUV laser at 165 nm was generated by a frequency octupled 1319 nm Nd:YAG laser. A maximum average output power of 6.8 mW at 165 nm was achieved. Numerical simulation of the ns KBBF SHG process was performed. The calculated VUV power was in good agreement with experimental data. Abstract: A high power nanosecond (ns) vacuum-ultraviolet (VUV) laser at 165 nm was demonstrated by means of a frequency-octupled 1319 nm Nd:YAG laser with a thick KBe2 BO3 F2 crystal. A 6.8 mW maximum output power at 165 nm was attained in the experiment, which is to our knowledge the highest power for all solid state lasers below 170 nm. The 165 nm output power versus the 330 nm pump power was simulated. The calculated result was well consistent with experimental data. Meanwhile, the dependence of 165 nm output power on the KBBF effective length was investigated theoretically. It was found that the thickness of KBBF crystal used in our experiment is close to the optimal thickness, which allows to creating the high VUV output power. We used the simulation further to analyze the pulse width, beam quality factor and beam spatial intensity profile of the generated 165 nm radiation.